Polar bear vs. grizzly bear - Pallotta, Jerry; Bolster, Rob. (New York : Scholastic, 2010)
Contains facts about polar bears and grizzly bears, comparing such aspects as their sizes, brain structure, and abilities.
"This edition is available for distribution only through the school market"--P. [4] of cover.
Keywords: Polar bear -- Juvenile literature; Grizzly bear -- Juvenile literature